2015
DOI: 10.15344/2455-3867/2015/104
|View full text |Cite
|
Sign up to set email alerts
|

Humor Styles in Indian University Students

Abstract: This study examined the relationship between humor styles, self-esteem and humor perception in India. The Humor Styles Questionnaire and the Rosenberg Self-esteem scale were used to survey 102 university students in India. Participants were also required to rate on importance of humor and their own level of humor. Results indicated that Indian university students tend to use more adaptive humor styles (affiliative humor and self-enhancing humor) than maladaptive humor styles (aggressive humor and self-defeatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Past research demonstrated that affiliative humor and self-enhancing humor styles were positively associated with psychological well-being (Hiranandani & Yue, 2014b;Yue, Wong, et al, 2014;Yue, Liu, et al, 2014;Jovanovic, 2011;Kazarian & Martin, 2004). Affiliative and self-enhancing humor were also found to be correlated with higher subjective happiness , higher selfesteem (Hiranandani & Yue, 2014a, 2014bOzyesil, 2012;, and lower depression (Frewen, Brinker, Martin, & Dozois, 2008;Kuiper & McHale, 2009). Specifically, affiliative humor and self-enhancing humor was found to be significantly and positively associated with subjective happiness in Chinese samples .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Past research demonstrated that affiliative humor and self-enhancing humor styles were positively associated with psychological well-being (Hiranandani & Yue, 2014b;Yue, Wong, et al, 2014;Yue, Liu, et al, 2014;Jovanovic, 2011;Kazarian & Martin, 2004). Affiliative and self-enhancing humor were also found to be correlated with higher subjective happiness , higher selfesteem (Hiranandani & Yue, 2014a, 2014bOzyesil, 2012;, and lower depression (Frewen, Brinker, Martin, & Dozois, 2008;Kuiper & McHale, 2009). Specifically, affiliative humor and self-enhancing humor was found to be significantly and positively associated with subjective happiness in Chinese samples .…”
Section: Introductionmentioning
confidence: 94%
“…Humor is a complex and multidimensional construct involving a combination of cognitive, emotional, and behavioral components (Martin & Lefcourt, 2004). It allows people to shift their attention in dealing with stressful situations (Levenson, 1994) and could serve as a special form of playfulness rather than an identical construct of fun-seeking (Hiranandani & Yue, 2014a, 2014b; Martin, 2003; Proyer & Ruch, 2011). In the West, humor was found to be an important predictor as well as a powerful outcome of playfulness (Proyer & Ruch, 2011), that is, highly playful adults were found to be humorous, outgoing, and happy (Barnett, 2007).…”
Section: Introductionmentioning
confidence: 99%